COMORBID PSYCHIATRIC DISORDERS AS AN EFFICIENCY FACTOR OF TREATMENT AND REHABILITATION OF CARDIAC PATIENTS - N. N. Petrova (Scientific Сentre for Family Health and Human Reproduction Problems, 2016)
On the sample of 90 patients with chronic heartfailure at the stage of stabilization we studied the influence of concomitant depressive and anxiety disorders on functional ability, quality of life and adherence to therapy. In our investigation we used the integrated and interdisciplinary approach to evaluation of psychosomatic status of patients, including test six minute walk, the method of clinical-scale evaluation, and an expert evaluation by a doctor. The data were processed using the program Microsoft Office Excel 2007 statistical software package SPSS Statistics 17.0. Significant frequency of anxious, depressive and comorbid anxiety and depressive disorders, which affect compliance and aggravate the functioning of the patients, was confirmed. It is shown that the results of treatment and rehabilitation activities are mediated by the presence and severity of anxiety and depressive disorders.